E-Catalog: Business Process Re-Engineering of Avon (M) Product Catalog Distribution Process - Siti Fatimah, Yusof (2011)
The traditional printed paper based product catalog is restricted to customers and places, which is difficult to handle in addition to time and cost of printing, storage area and shipping. Thus, this study attempts to present results of a Business Process Re-engineering (BPR) of a direct selling catalog distribution that is able to eliminate such physical limitations and enable the distribution business process to become more efficient. Incorporating e-catalog as an outcome of the BPR shows that the business process can be simplified from 32 activities to 13 activities. With this approach the percentage of process efficiency rate for business process selected has been increased dramatically from 20% up to 86% and also reduced the waiting rate from 55% to 7%. In order to rate the usefulness of e-catalog, 30 respondents from Avon dealers were selected to test the e-catalog prototype. The final result indicated that Business Process Re-engineering has the capability to simplify fairly complex manual and paper-based processes, resulting in better, more efficient e-catalog distribution system.